Estimates of Phytoplankton carbon from high resolution optical sensors in the Southern Ocean - Ogunkoya, Ayodele Gilbert (Marine Research (MA-RE) Institute, 2015)
Phytoplankton is an important component of the oceanic carbon cycle, and deriving a good estimate of its carbon biomass (Cphyto) at ocean scale is difficult due to the lack of automatic sampling procedures. This is particularly difficult in the Southern Ocean, where winter conditions limit the sampling. This study explored the opportunity of using a high resolution data from the glider tracks in the Sub-Antarctic Zone of the Southern Ocean. The data consisted of particulate backscattering and chlorophyll and four different methods of estimating phytoplankton carbon were used, three of them based on backscattering (named 30%POC, B05 and M13) and one on chlorophyll (S09). The methods are different in their empirical formulations and source of original data. Three methods showed similar results despite the fact that one of them makes use of chlorophyll to derive Cphyto. Method M13 doubles that of the 3 other methods (~80mg C m-³ vs 40-50 mg C m-³). It was observed that discrepancy between M13 and the other 3 methods decreases with depth and when biomass was low (~0.25 mg Chl-a m-³) e.g., at depth 80 m. Investigating the drivers of variability in chl-a:C phyto ratios with depth and MLD shows little response and highlighted the need for more research in this region. Although M13 has a very low chl-a:Cphyto ratios, the range of variability was similar to that of the 30%POC and B05 methods and likely driven by variability in light and Fe limitation and changes in community structure. Despite a similar magnitude, the S09 method show a tight constrain in chl-a:Cphyto ratios that were methodologically driven and thus less sensitive to physiological adjustments in cellular chl-a:Cphyto ratios. The analysis also confirms that each oceanic region has factors that drive their variability and care needs to be taken when applying a method that was derived from one oceanic region to another.